Fusarium merismoides Corda. - A New Record of Anamorphic Fungus for Bangladesh - Shamsi, Shamim; Hosen, Md Delwar (Journal of Bangladesh Academy of Sciences, 2016)
Abstract not available Journal of Bangladesh Academy of Sciences, Vol. 40, No. 2, 207-209, 2016